153k views
4 votes
Hi May I know how to solve this step by step please

Hi May I know how to solve this step by step please-example-1

1 Answer

2 votes

Answer:

2, 3 , 5, 7

Explanation:

2(x - 2)/3 < (x + 1)/2 < 3(5x + 6)/4

Considering:

2(x - 2)/3 < (x + 1)/2

<=>(2x - 4)/3 < (x + 1)/2

<=> (2x - 4)*2 < (x + 1)*3

<=> 4x - 8 < 3x + 3

<=> 4x - 3x < 8 + 3

<=> x < 11

Considering:

(x + 1)/2 < 3(5x + 6)/4

<=>(x + 1)/2 < (15x + 18)/4

<=>(x + 1)*4 < (15x + 18)*2

<=> 4x + 4 < 30x + 36

<=> 4x - 30x < 36 - 4

<=> -26x < 32

<=> 26x > -32

<=> x > -32/26

=> -32/26 < x < 11

The prime numbers satisfy the above inequalities: 2, 3 , 5, 7

User DILP
by
5.3k points